Total Synthesis of Tiacumicin B: Implementing Hydrogen Bond Directed Acceptor Delivery for Highly Selective β‐Glycosylations. (25th February 2020) - Norsikian, Stéphanie; Tresse, Cedric; François‐Eude, Marc; Jeanne‐Julien, Louis; Masson, Guillaume; Servajean, Vincent; Genta‐Jouve, Grégory; Beau, Jean‐Marie; Roulland, Emmanuel
Abstract: A total synthesis of tiacumicin B, a natural macrolide whose remarkable antibiotic properties are used to treat severe intestinal infections, is reported. The strategy is in part based on the prior synthesis of the tiacumicin B aglycone, and on the decisive use of sulfoxides as anomeric leaving groups in hydrogen‐bond‐mediated aglycone delivery (HAD). This new HAD variant permitted highly β‐selective rhamnosylation and noviosylation. To increase convergence, the rhamnosylated C1–C3 fragment thus obtained was anchored to the C4–C19 aglycone fragment by adapting the Suzuki–Miyaura cross‐coupling used for the aglycone synthesis. Ring‐size‐selective macrolactonization provided a compound engaged directly in the noviolysation step with virtually total β selectivity. The final efficient removal of all the protecting groups provided synthetic tiacumicin B. Abstract : Eine Totalsynthese von Tiacumicin B, einem natürlichen Makrolid mit bemerkenswerten antibiotischen Eigenschaften zur Behandlung schwerer Darminfektionen, wird vorgestellt. Die Strategie basiert auf der Synthese des Tiacumicin‐Aglykons und der Verwendung von Sulfoxiden als anomere Abgangsgruppen im wasserstoffbrückenvermittelten Aglykon‐Transfer. DG= dirigierende Gruppe.